Demolishing Dikes: Multiple Streams and Policy Discourse Analysis. Issue 1 (29th October 2015) - Winkel, Georg; Leipold, Sina
Abstract : The Multiple Streams Framework (MSF) is an influential theoretical framework for the analysis of policymaking processes, in particular agenda setting. It has inspired numerous empirical applications, which result in substantially different interpretations, for instance, of what exactly the "streams" encompass, how policy entrepreneurship is practiced, and how the coupling of distinct streams works. This article undertakes a systematic assessment of the MSF's core elements from the perspective of policy discourse analysis. Through an understanding of "streams" as discursive patterns, and policy discourses as (historical) couplings of the streams, a new and theoretically consistent interpretation of streams and likely connections between them is offered. One specific focus is on Kingdon's concept of policy entrepreneurship and how it relates to ideas of agency in discourse analysis. Drawing on the recently proposed Discursive Agency Approach, we discuss how concepts such as subject positions in discourses, agent subjectivization via the dialectic interplay of individual characteristics and structural forces, and discursive practices and strategies relate to and can possibly complement the MSF. Particular emphasis is given to the metaphors the MSF provides. In conclusion, the article demonstrates that a post‐positivist perspective holds great potential for enriching the MSF theoretically and strengthening it analytically.